3D printed horn antenna using direct metal laser melting technique for millimetre wave applications - Muataz W. Sabri; M. K. A. Rahim; F. Zubir (IAES Indonesian Section, 2019)
A 3D printed horn antenna at ka-band is presented in this paper. The horn antenna is well known for high gain performance. The performance of the horn antenna manufactured using 3D printed technology is investigated in this work. The horn is designed based on WR-28 waveguide standard. The proposed horn is simulated by computer simulation technology (CST) software and fabricated using 3D printing direct metal laser melting technique. The 3D printing technique gives the antenna an advantage of being not just rapid manufactured but also low-cost and lightweight. However, several works reported on 3D printed devices highlight the effects of surface roughness and dimensional tolerance on the performances. Therefore, the printed horn is profiled to correlate the surface roughness and dimension tolerance towards the performance. The printed horn is measured using standard VNA. The results showed that the measured performance agreed fairly with the simulation with directive radiation pattern at 15 dBi gain. The printed horn has a weight of less than 130g and considerably working at Ka band regardless of the surface roughness resulted from the fabrication process.